2008
DOI: 10.1007/s00213-008-1178-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel procedure for assessing the effects of drugs on satiation in baboons: effects of memantine and dexfenfluramine

Abstract: Rationale-Procedures for studying the effects of medications on satiation will assist the development of obesity medications.Objectives-Develop a procedure for measuring satiation during consumption of bland and highly palatable food, and determine the effect of acute intramuscular administration of dexfenfluramine (DFEN), which increases serotonin levels, and memantine (MEM), which blocks N-methyl-Daspartate receptors.Methods-A modified progressive ratio (PR) procedure was used to track changes in reinforcing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 52 publications
8
15
0
Order By: Relevance
“…Results of the present study, as well as previous studies using animal models (Bisaga et al 2008; Foltin et al 2008), suggest that memantine may have a uniquely attractive profile of clinical effectiveness. Initial uncontrolled clinical observations confirm the safety and potential effectiveness of memantine in reducing binge-eating with less effect on weight (Brennan et al 2008; Hermanussen and Tresguerres 2005).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Results of the present study, as well as previous studies using animal models (Bisaga et al 2008; Foltin et al 2008), suggest that memantine may have a uniquely attractive profile of clinical effectiveness. Initial uncontrolled clinical observations confirm the safety and potential effectiveness of memantine in reducing binge-eating with less effect on weight (Brennan et al 2008; Hermanussen and Tresguerres 2005).…”
Section: Discussionsupporting
confidence: 83%
“…We have previously shown in baboons, that single doses of memantine and MTEP produce decrease in the consumption of highly palatable food (candy) comparable to effects of dexfenfluramine, another prototypic binge-eating reducing medication (Bisaga et al 2008; Foltin et al 2008). The second goal of the present study was therefore to evaluate the effects of the NMDA receptor antagonist memantine and the mGluR5 antagonist MTEP and to compare those effects to the effects of sibutramine in the limited-access animal model of binge-eating of highly palatable food (lard) and on the consumption of chow available at all times.…”
Section: Introductionmentioning
confidence: 98%
“…Notably, a large body of evidence shows that memantine reduces the reinforcing and rewarding effects of drugs of abuse (Hart et al, 2002;Hyytia et al, 1999;Popik et al, 2003;Sabino et al, 2013). Interestingly, a few studies have suggested the ability of memantine also to reduce excessive intake of palatable food Foltin et al, 2008;Popik et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although the baboons were not food deprived, other than during the dark cycle, the procedure limited the variability in the pattern of food intake. Limiting the rate of food intake by forcing breaks between eating the 20 candies has been shown to provide an eating baseline that was sensitive to the hypothesized effects of drugs on satiation [27]. …”
Section: Introductionmentioning
confidence: 99%